Bronchiolitis obliterans syndrome in lung transplantation - Glanville, Allan R.; Meyer, Keith C. (Respiratory Medicine, 2013)
Bronchiolitis Obliterans Syndrome in Lung Transplantation presents the most current and up-to-date evidence regarding the diagnosis and management of BOS.  In-depth chapters provide readers with a comprehensive understanding of the definition and changing perceptions of the nature of BOS as a clinical and pathologic entity, immune and non-immune mechanisms that have been identified as risk factors for the development of BOS, and interventions that may prove to be clinically useful for the prevention or treatment of BOS.  In addition to outlining the current state of knowledge, each chapter provides the reader with the most current and ongoing research in the field as well as identifies areas where future research is needed. Written by an international group of expert authors, Bronchiolitis Obliterans Syndrome in Lung Transplantation is an important new text, that is essential reading for pulmonologists, primary care practitioners, respiratory care practitioners and clinical researchers.